1990
DOI: 10.1182/blood.v76.1.221.221
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-thalassemia caused by a large (62 kb) deletion upstream of the human alpha globin gene cluster

Abstract: We describe a family in which a-thalassemia occurs in association with a deletion of 62 kilobases from a region RNA analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(22 citation statements)
references
References 37 publications
2
17
0
2
Order By: Relevance
“…They are co‐ordinately regulated by the 350‐bp major regulatory element (αMRE), better known as HS‐40, located upstream of the structural genes (Forrester et al , 1987; Grosveld et al , 1987; Higgs et al , 1990). The importance of these sequences became evident from large deletions that occurred upstream of the structural genes which abolished the globin gene expression in cis (Hatton et al , 1990; Liebhaber et al , 1990; Wilkie et al , 1990; Romao et al , 1991, 1992). Genomic footprinting has demonstrated the formation in vivo of specific nuclear factor DNA complexes at a subset of these sequence motifs in erythroid cells (Fig 1) (Strauss et al , 1992).…”
mentioning
confidence: 99%
“…They are co‐ordinately regulated by the 350‐bp major regulatory element (αMRE), better known as HS‐40, located upstream of the structural genes (Forrester et al , 1987; Grosveld et al , 1987; Higgs et al , 1990). The importance of these sequences became evident from large deletions that occurred upstream of the structural genes which abolished the globin gene expression in cis (Hatton et al , 1990; Liebhaber et al , 1990; Wilkie et al , 1990; Romao et al , 1991, 1992). Genomic footprinting has demonstrated the formation in vivo of specific nuclear factor DNA complexes at a subset of these sequence motifs in erythroid cells (Fig 1) (Strauss et al , 1992).…”
mentioning
confidence: 99%
“…Previous work has also shown that genes are deregulated in cells of ATR-X patients and ATRX mutant mice [203,204]. Two possible mechanisms by which ATRX can act as a transcriptional regulator have been demonstrated [193,205].…”
Section: Alpha-thalassemia Mental Retardation X-linked Syndrome (Atr-x)mentioning
confidence: 97%
“…Thalassaemias are characterized by inherited mutations leading to a reduction of the synthesis of α- (α-thalassaemia) or β-globin (β-thalassaemia) chains from one allele. Human genetics is a good approach to identify functional remote regulatory elements, and original observations were made in patients with α- and β-thalassaemia [22] [24] . In most cases, a deletion removing a globin gene is the cause of this down-regulation, but in some rare cases, the genes (including their promoters) remain intact [25] .…”
Section: Structure Of the α-Globin Locusmentioning
confidence: 99%
“…Due to the nature of the disease (anaemia), it was however difficult to perform a number of experiments on primary cells because of the large amount of material required and also because this material is only available for a limited time. For this reason, interspecific hybrids were produced by the fusion of a human immortalised B cell (Epstein-Barr virus [EBV] infected) with the mouse MEL cell line described earlier [24] , [28] , [64] , [65] .…”
Section: Role(s) Of the Remote Regulatory Sequencesmentioning
confidence: 99%